2016
DOI: 10.1590/0103-6440201600495
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Restored Endodontically Treated Teeth in Relation to Periodontal Status

Abstract: The aim of the present study was to investigate the success and survival of restored endodontically treated teeth (ETT) in a general practice environment related to periodontal parameters. Data from 360 restored ETT treated between 2000 and 2011 were collected. Dates of interventions like restorations, repairs, replacements and extractions were recorded. Additionally, general information about patients and dentitions as well as periodontal status was recorded. Success was analyzed using Kaplan-Meier statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
(14 reference statements)
0
14
0
Order By: Relevance
“…In sites with greater bone loss, a poorer treatment response has been reported regarding probing pocket depth reduction . Also, periodontal disease (pockets > 5 mm) around endodontically treated teeth appears to be an extra risk factor, which can affect tooth survival . In the present study, patients that did not have a successful treatment response had endodontic treatment, which varied between 8% and 11% dependent on tooth type (Table ).…”
Section: Discussionmentioning
confidence: 62%
“…In sites with greater bone loss, a poorer treatment response has been reported regarding probing pocket depth reduction . Also, periodontal disease (pockets > 5 mm) around endodontically treated teeth appears to be an extra risk factor, which can affect tooth survival . In the present study, patients that did not have a successful treatment response had endodontic treatment, which varied between 8% and 11% dependent on tooth type (Table ).…”
Section: Discussionmentioning
confidence: 62%
“…There is little scientific evidence that associates successful endodontic treatment with the maintenance of these teeth in the oral cavity in the long term. [ 11 12 ] Considering that periodontal diseases frequently appear as one of the main factors associated with the loss of endodontically treated teeth,[ 9 10 11 ] the aim of this study was to evaluate the incidence of periodontal compromise in teeth indicated for undergoing endodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among the main reasons associated with the loss of endodontically treated teeth, periodontal diseases frequently appear as one of the most relevant types. [ 9 10 11 ] However, strangely enough, there is limited scientific evidence about the importance of periodontal status in relation to successful endodontic treatment and maintenance of endodontically treated teeth in the long term. [ 11 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…The increased risk of tooth loss was 3,1 for endodontically treated teeth with moderate periodontitis. Skupien et al (37) in their study also confirmed the importance of healthy periodontal status on the survival of endodontically treated teeth. Periodontal pocket depth was found to be a significant factor in the survival of restored endodontically treated teeth.…”
Section: Resultsmentioning
confidence: 59%